Studies on the inhibition of AmpC and other β-lactamases by cyclic boronates - Cahill, Samuel T.; Tyrrell, Jonathan M.; Navratilova, Iva Hopkins; Calvopiña, Karina; Robinson, Sean W.; Lohans, Christopher T.; McDonough, Michael A.; Cain, Ricky; Fishwick, Colin W.G.; Avison, Matthew B.; Walsh, Timothy R.; Schofield, Christopher J.; et al. (Biochimica et biophysica acta. General subjects, 2019)
The β-lactam antibiotics represent the most successful drug class for treatment of bacterial infections. Resistance to them, importantly via production of β-lactamases, which collectively are able to hydrolyse all classes of β-lactams, threatens their continued widespread use. Bicyclic boronates show potential as broad spectrum inhibitors of the mechanistically distinct serine- (SBL) and metallo- (MBL) β-lactamase families. Using biophysical methods, including crystallographic analysis, we have investigated the binding mode of bicyclic boronates to clinically important β-lactamases. Induction experiments and agar-based MIC screening against MDR-Enterobacteriaceae (n = 132) were used to evaluate induction properties and the in vitro efficacy of a bicyclic boronate in combination with meropenem. Crystallographic analysis of a bicyclic boronate in complex with AmpC from Pseudomonas aeruginosa reveals it binds to form a tetrahedral boronate species. Microbiological studies on the clinical coverage (in combination with meropenem) and induction of β-lactamases by bicyclic boronates further support the promise of such compounds as broad spectrum β-lactamase inhibitors. Together with reported studies on the structural basis of their inhibition of class A, B and D β-lactamases, biophysical studies, including crystallographic analysis, support the proposal that bicyclic boronates mimic tetrahedral intermediates common to SBL and MBL catalysis. Bicyclic boronates are a new generation of broad spectrum inhibitors of both SBLs and MBLs. •Bicyclic boronate structures reveal mechanism of the broad spectrum β-lactamase inhibition by this new drug class.•Bicyclic boronates do not manifest detectable β-lactamase induction in some bacteria.•Microbiological studies reveal promising clinical coverage for this class of β-lactamase inhibitor.